2004
DOI: 10.2337/diabetes.53.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Glucose-Stimulated Insulin Secretion With Aging Is Independent of Insulin Action

Abstract: While the incidence of diabetes increases with age, a decrease in ␤-cell function independent of age-related insulin resistance has not been conclusively determined. We studied insulin secretion (by hyperglycemic clamp) in 3-, 9-, and 20-month-old chronically catheterized, awake, Sprague Dawley (SD) rats (n ‫؍‬ 78). Insulin action was modulated in a group of old rats by caloric restriction (CR) or by surgical removal of visceral fat (VF؊). During the first 2 h of the clamp (11 mmol/l glucose), insulin secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 48 publications
5
60
1
Order By: Relevance
“…In particular, aged mice were insulin-resistant and glucoseintolerant, although intolerance was only observed when aged mice were forced to release more insulin; for example, after a higher glucose load (37,38). Our results concur with those of several previous studies (3,5,6,39) but contrast with studies reporting insulin secretory defects with age (1,2,4,8). The discrepancies in the literature may be explained by the confounding influence of the systemic environment (10).…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In particular, aged mice were insulin-resistant and glucoseintolerant, although intolerance was only observed when aged mice were forced to release more insulin; for example, after a higher glucose load (37,38). Our results concur with those of several previous studies (3,5,6,39) but contrast with studies reporting insulin secretory defects with age (1,2,4,8). The discrepancies in the literature may be explained by the confounding influence of the systemic environment (10).…”
Section: Discussioncontrasting
confidence: 57%
“…S3 (50)]. A dysfunctional vasculature also helps explain why there is a discrepancy between in vitro data showing no deterioration of insulin secretion with age (5) and in vivo studies reporting lower plasma insulin levels in response to hyperglycemia in aged mice (6,10).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Elevated blood lipids are known to impair insulin secretion. 27,28 In the current study, we observed a statistically significant correlation between TGs, total cholesterol, and HDL with the basal derived measures of b-cell function. However, the physiological relevance of this observation is uncertain given the weak correlation.…”
Section: Discussionmentioning
confidence: 65%
“…This result is consistent with experimental data from different species showing that aging per se is associated with a continuous decrease in basal insulin release. The magnitude of this effect is enough to develop abnormalities in glucose metabolism [36][37][38] . Body weight increased in the Control and MS rats; nevertheless, the difference between the groups was not significant even though the diet of the sucrose-fed rats was hypercaloric ( Table 1).…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 99%